1991
DOI: 10.1056/nejm199110033251405
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Corticosteroid Injections into Facet Joints for Chronic Low Back Pain

Abstract: We conclude that injecting methylprednisolone acetate into the facet joints is of little value in the treatment of patients with chronic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
309
1
17

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 481 publications
(333 citation statements)
references
References 17 publications
6
309
1
17
Order By: Relevance
“…Lilius et al [26], reported 'few' side effects but do not specify what they were. Carette et al [27], report some localised pain near injection site. Ribeiro et al [31] report adverse events, noting there were no significant differences between groups.…”
Section: Conservative Treatmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lilius et al [26], reported 'few' side effects but do not specify what they were. Carette et al [27], report some localised pain near injection site. Ribeiro et al [31] report adverse events, noting there were no significant differences between groups.…”
Section: Conservative Treatmentsmentioning
confidence: 99%
“…We included six trials with a total of N = 434 participants (range 18-109 participants); Lilius [26], Carette [27], Mayer [28], Celik [29], Kawu [30] and Ribeiro [31].…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations